Do temporary workers receive risk-premiums? Assessing the wage effects of fixed-term contracts in West-Germany by matching estimators compared with parametric apporaches - Tobias Hagen (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2001)
The wage effects of fixed-term contracts (FTCs) are analysed with the GSOEP for West Germany. Different estimators which take into account selection bias are used. It is shown that propensity score matching estimators which are usually applied for the evaluation of active labour market programmes are well-suited for the analysis of this topic, whereas parametric approaches find unrealistically large negative effects. The empirical evidence rejects compensating wage differentials as well as strong negative wage effects of FTCs.
Keywords: J31; C35; C14; 330; Fixed-term Employment; Wage Differentials; Propensity Score Matching; Lohnstruktur; Befristeter Arbeitsvertrag; Risikoprämie; Schätzung; Deutschland